(3aQb GdWH dLGdjfhSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3Ef HYV GdfGS bSe GdWH bSejf , hHYVge bSeg NeSI CbSGe hGdPjf bSehg bSejf bGdhG s
(3BNQgG (B:s
(3Ef cGfJ eGOJg eGOI QbjbI eQTM hLQi efg HYVgG , hEf cGfJ ZdjXI de jQTM TF efgG s
(3gh GdcJGH GdChd ef LhGeY GdcJH GdSJI YTQ dLGdjfhSs
(3GdJi cGfJ JbQC Ydi GdeYdejf HGdGScfOQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B1 - (3U (B205 ; GALS - (3GdLRA (B1 - (3U (B366 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B137 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjG UhajG (B(3588(1)) s
Keywords: (3GdWHs